1988
DOI: 10.1063/1.453837
|View full text |Cite
|
Sign up to set email alerts
|

Counterion condensation in micellar and colloidal solutions

Abstract: Asymptotic solutions are obtained to the Poisson–Boltzmann equation for large, highly charged spheres in an ionic solution. It is proved that as the size of the sphere is increased, keeping the surface charge density fixed, there is a critical value for the radius beyond which counterion condensation sets in. This critical radius is much larger than the Bjerrum length but small compared to the Debye length and depends on the ionic strength. An expression is derived for the effective charge. When the radius bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 13 publications
3
61
0
Order By: Relevance
“…One early study (Zimm and Lebret, 1983) suggested that although likely with cylindrical and planar surfaces, counterion condensation does not occur with particles of spherical geometry. The present findings and those by Loux (1985) are consistent with observations by Ramanathan (1988) that condensation does occur on spherical particles when the particle radius is large relative to the dimensions of the diffuse layer. From another perspective, when the term k*r is large, a spherical particle can be viewed as an ''infinite plane'' without edge effects and hence, also can experience counterion condensation.…”
supporting
confidence: 82%
“…One early study (Zimm and Lebret, 1983) suggested that although likely with cylindrical and planar surfaces, counterion condensation does not occur with particles of spherical geometry. The present findings and those by Loux (1985) are consistent with observations by Ramanathan (1988) that condensation does occur on spherical particles when the particle radius is large relative to the dimensions of the diffuse layer. From another perspective, when the term k*r is large, a spherical particle can be viewed as an ''infinite plane'' without edge effects and hence, also can experience counterion condensation.…”
supporting
confidence: 82%
“…(12) still yields a reasonable estimate for Z sat eff (κa), specially for high values of the parameter κa. In the limit of small κa, both expressions (12) and (14) differ notably from the PB saturation charge which diverges, as shown by Ramanathan [28], as:…”
Section: A Planar Casementioning
confidence: 98%
“…At intermediate salt concentration, κ D a 1, the behavior is non-monotonic (and will not be detailed here), while for κ D a 1 [but not smaller than exp(−l B /2a)], Q eff saturates at a value, Ramanathan (1986Ramanathan ( , 1988) that does not depend on Q itself:…”
Section: The Non-linear Pb Solution: Counter-ion Only and Manning Conmentioning
confidence: 99%